IMPACT OF ASPARTAME CONSUMPTION ON NEUROTRANSMITTERS IN RAT BRAIN - Baothman, Othman A.S.; Moselhy, Said S.; Al-Shehri, Sharifah H.; AL-Malki, Abdulrahman L (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Aspartame (APM), a common artificial sweetener, has been used for diabetic subjects and body weight control for a long time. The goal of the present study was to evaluate the impact of APM consumption on neurotransmitters and oxidative stress in rat’s brain. Materials and Methods: Four groups of male Wistar albino rats was used: Group1, control (Rats fed on normal diet). Group 2: Rats were received aspartame (50 mg/kg b w). Group3: Rats were received aspartame (75 mg/kg b w). Group 4: Rats were received aspartame (125 mg/kg b w). Five rats were decapitated after 10, 20, 30 and 40 days from start of experiment. Blood and brain tissue were collected for biochemical analysis. Biochemical analysis of brain tissue includes neurotransmitters (Acetylcholine, epinephrine, norepinephrine, γ-aminobutyric acid and serotonin). Serum for determination of lipid peroxidation (MDA), reduced glutathione and superoxide dismutase (SOD). Results: the data obtained showed that antioxidant activities (SOD and GSH) were reduced significantly (p<0.001) while malondialdhyde (MDA) level was increased compared with control. Brain neurotransmitters levels (serotonin, GABA and dopamine) were reduced significantly compared with control (p<0.001, <0.01) after consumption of APM. However, the level of acetylcholine and norepinephrine increased in rats fed AMP compared with control (p<0.001). The effect of APM is dose dependent. Conclusion: Consumption of APM for a long time increased oxidative stress in brain tissue and disruption in neurotransmitters that affect physiological functions.